IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN KOGNITIF SISWA PADA MATA PELAJARAN IPAS DI KELAS V MI - Dewi Salsabila Rohmah; Imam Muslih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal implementation of the Problem Based Learning (PBL) model in IPAS (Integrated Science and Social Studies) learning, which has an impact on students’ cognitive abilities, particularly higher-order thinking skills. The purpose of this study was to describe the implementation of the PBL model and to analyze students’ cognitive abilities facilitated through PBL based on the revised Bloom’s Taxonomy (C1–C6). This research employed a qualitative approach with a descriptive research design. The subjects of this study were a fifth-grade teacher and students of MI As-Salam Bogo Nganjuk. Data were collected through observation, interviews, and documentation, while data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results showed that the implementation of PBL had been carried out through stages including problem orientation, student organization, investigation, presentation of results, and evaluation; however, it had not been implemented optimally and consistently. Students’ cognitive abilities were still dominated by lower-order thinking skills, namely remembering (C1) and understanding (C2), while higher-order thinking skills such as applying (C3), analyzing (C4), evaluating (C5), and creating (C6) had not developed optimally. These findings were influenced by students’ limited understanding of problems, low participation in discussions, and teachers’ constraints in managing problem-based learning. Therefore, improvements in the implementation of PBL are needed to enhance students’ cognitive abilities more effectively.